PENERAPAN METODE PEMBELAJARAN INSIDE-OUTSIDE CIRCLE PADA MATERI PENGUKURAN UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI MATEMATIS SISWA KELAS V SDN KEBON BAWANG 03 JAKARTA UTARA - Dahlia, Yeni; Amelia, Winda (FKIP Universitas Al Washliyah Medan, 2025)
This study aims to improve the mathematical communication skills of fifth grade students through the application of the inside-outside circle learning method on measurement material at SDN Kebon Bawang 03 Jakarta Utara in the 2024/2025 Academic Year. This study was conducted using the type of classroom action research (CAR) with 34 fifth grade students as research subjects whose data were collected using observation and documentation techniques. The results of the study obtained a score of students mathematical communication skills with an average of 37.64% which is included in the “less” category, then corrective actions were carried out in cycle I showing students mathematical communication skills with an average of 65.52% which is included in the “good” category, and improvements were made again in cycle II with the results of students mathematical communication skills with an average of 81.29% which is included in the “very good” category. This means that this study was declared successful because it had achieved the desired success criteria with an average score percentage reaching 80%. Thus, it is concluded that there was an increase in the mathematical communication skills of grade V students after the inside-outside circle method was applied to the measurement material at SDN Kebon Bawang 03 Jakarta Utara.